Improving Naval aviation depot responsiveness - Brauner, Marygail K., 1947-; Relles, Daniel A.; Galway, Lionel A., 1950-; Rand eBooks (Santa Monica, CA : RAND, 1992)
This report examines the consequences of increasing the Navy depot's role in the logistics system by directing its resources toward the day-to-day needs of the fleet. Using a simulation that examined whether mission capability could be improved during a 90-day war through some combination of responsive stock management, proactive use of depot repair capabilities, and shortened transportation pipelines between carriers and depots, the authors found that priority repair at the depot can make on important difference in mission capability, that shortened pipelines can have large effects on mission capability, and that constructing an aviation consolidated allowance list (AVCAL) based on aircraft availability goals may offer promise for maximizing aircraft availability per dollar spent. The study also concluded that data synthesis is a missing ingredient in the Naval aviation logistics management system that inhibits the depot's ability to react quickly in support of sudden demand peaks.
"Arroyo Center"--Cover.
Includes bibliographical references (p. 59-61).
Available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Navy -- Aviation supplies and stores; United States. -- Navy -- Combat sustainability; United States. -- Navy -- Equipment -- Maintenance and repair; United States. -- Navy -- Inventory control; Aircraft carriers -- United States; Electronic books